Pengaruh Penggunaan Lembar Kerja Peserta Didik (LKPD) Berbasis Proyek terhadap Hasil Belajar Peserta Didik - Ambyar Ambyar; Ranti Ermina Sari; Liza Mustika Sari; Fadhilah Majid Saragih; Deviana Ridhani (Departement of Mathematics Education, 2023)
The purpose of this study was to determine the effect of using Student Worksheets (LKPD) Class XI SMK 4 Payakumbuh majoring in Software Engineering (RPL) with material for making forms on web pages for Mobile Device Web Programming subjects. This research was conducted at SMK 4 Payakumbuh on October 15 and November 15 2022. The analytical method used was a pure experiment with participants from each class in the Class XI RPL class which consisted of around 2 classes with 23 students each. The two sample groups used in cluster random sampling were class IX RPL 1 which was designated as the Experimental Group, and class IX RPL 2 which was designated as the control group. The average value of each is as follows: the Control Class is 77.78 and the Experimental Class is 85.48. the research produced a Sig value <0.05 so it can be concluded that the use of project-based worksheets has an effect on student learning outcomes.